Enter Her Novice World: A Narrative Study on The Life of a Teenage Student–Mother - Christian Paul G. Abalos; Yvrin Gabriel D. Lagcao; Seth Nahzier S. Perocho; Adonis S. Besa; Ladymer L. Peñaflor (Universitas Pendidikan Indonesia (UPI), 2023)
This study unraveled the challenges of a teenage mother while studying as a senior high school student amidst the tremors of the pandemic. In doing so, a qualitative narrative research design was used in gathering the data, and an unstructured interview was done with the main participant. The listed responses were scrutinized to formulate a general conclusion regarding the overall condition of the teenage mother. Based on the findings, it was revealed that the teenage student-mother is prone to conflicts, and to combat these conflicts, perseverance along with hard work is a must. For the most part, it has been established that the amount of support received by the teenage student-mother is one of the major reasons that contribute to their overall state because in every aspect of life they are involved in, their children will always be a part of them because they are the utmost priority of these teenage student-mothers. In general, the researchers concluded that in the participant’s time in distance learning, her parenting was not affected that much by her school work. With this being said, her positive attitude towards her grueling circumstance led to her overall success in both her motherly and academic duties. She was able to continue her studies and take care of her child all at once because of the new learning environment brought out by distance learning.